A79 CLINICAL VALIDATION OF THE SIMPLE CLASSIFICATION FOR OPTICAL DIAGNOSIS OF DIMINUTIVE AND SMALL COLORECTAL POLYPS. (26th February 2020) - Alaoui, A; Oumedjbeur, K; Djinbachian, R; Marchand, E; Marques, P; Hammar, C; Pohl, H; Bouin, M; Deslandres, E; Bouchard, S; von Renteln, D
Abstract: Background: Image enhanced endoscopy (IEE) allows for real-time optical diagnosis of colorectal polyps in order to replace histopathology. A novel classification system (SIMPLE classification) has recently been developed for optical diagnosis when using the novel Pentax Optivista IEE platform. Aims: The aim of this study was to evaluate the SIMPLE classification for optical polyp diagnosis in a prospective clinical study. Methods: Patients undergoing screening, diagnostic or surveillance colonoscopies were enrolled in the study. All colorectal polyps 1-10mm found underwent optical polyp diagnosis using the SIMPLE classification with either iScan or Optivista for image-enhanced endoscopy (IEE). Polyps were resected as per standard care and sent for histopathology analysis. Optical diagnosis and surveillance intervals were calculated based on SIMPLE criteria and compared to pathology-based results as reference. Primary outcome was the agreement of the surveillance intervals based on the SIMPLE classification with pathology-based surveillance intervals for 1-5mm colorectal polyps. Secondary outcomes included negative predictive value (NPV) for rectosigmoid adenoma, percentage of pathology avoided, percentage of post-colonoscopy immediate recommendations, and surveillance interval agreement, rectosigmoid NPV for 1-10mm polyps. Results: 399 patients (mean age: 62.4, 55.6% female) with 278 diminutive and 364 small polyps were evaluated in the study cohort. For ≤5mm polyps, agreement with pathology-based surveillance intervals was 93.5% [95% CI 91.1–95.9] (shorter: 4.5% [95% CI 2.5–6.5]; longer: 1.8% [95% CI 0.5–3.0]). NPV for rectosigmoid adenomatous polyps (including SSA) was 85.5% [95% CI 77.6–93.4]. Using Optical diagnosis and the SIMPLE classification, pathology analysis could be avoided in 61.5% [95% CI 56.9–66.2] of polyps and post-colonoscopy immediate surveillance interval recommendation could be given in 70.9% [95% CI 66.5–75.4] of patients. For ≤10mm polyps, agreement with pathology-based surveillance intervals was 92.2% [95% CI 89.6–94.9] (shorter: 5.5% [95% CI 3.3–7.8]; longer: 2.3% [95% CI 0.8–3.7]). NPV for rectosigmoid adenomatous polyps (including SSA) was 83.7% [95% CI 75.9–91.5]. Conclusions: The first clinical validation study using the SIMPLE classification in combination with Optivista or iScan IEE showed a high (≥90%) surveillance interval agreement compared to pathology. More than 60% of pathology could be avoided, and most patients could be given immediate surveillance intervals when using IEE in combination with the SIMPLE classification. Funding Agencies: NonePentax